2017
DOI: 10.17221/7/2017-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of forest fire risk using the Apriori algorithm and fuzzy c-means clustering

Abstract: Jafarzadeh A.A., Mahdavi A., Jafarzadeh H. (2017): Evaluation of forest fire risk using the Apriori algorithm and fuzzy c-means clustering. J. For. Sci., In this study we evaluated forest fire risk in the west of Iran using the Apriori algorithm and fuzzy c-means (FCM) clustering. We used twelve different input parameters to model fire risk in Ilam Province. Our results with minimum support and minimum confidence show strong relationships between wildfire occurrence and eight variables (distance from settlemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 31 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…In our study, the overall accuracy was 95%, the kappa coefficient was 0.93 and the AUC value was 0.81, suggesting the map is accurate and fit for purpose. The AUC value above 0.80 is considered highly accurate and well-accepted (Jafarzadeh et al, 2017). Tiwari et al, (2021) report similar results from India when comparing the AUC values under fuzzy-AHP, AHP and frequency methods of forest fire risk map where the highest AUC value was under fuzzy-AHP method (0.83).…”
Section: Discussionmentioning
confidence: 55%
“…In our study, the overall accuracy was 95%, the kappa coefficient was 0.93 and the AUC value was 0.81, suggesting the map is accurate and fit for purpose. The AUC value above 0.80 is considered highly accurate and well-accepted (Jafarzadeh et al, 2017). Tiwari et al, (2021) report similar results from India when comparing the AUC values under fuzzy-AHP, AHP and frequency methods of forest fire risk map where the highest AUC value was under fuzzy-AHP method (0.83).…”
Section: Discussionmentioning
confidence: 55%
“…FCM was used to map all of the variables into 3 clusters, namely low, medium and high. Their study concluded that there was a strong relationship between the forest fire clusters and the cluster of 8 input variables, including: distance from the settlements, population density, distance from a road, slope, standing dead oak trees, temperature, land cover and distance from farmland (Jafarzadeh, Mahdavi, & Jafarzadeh, 2017). Differing from the aforementioned studies, in this paper we apply global satellite data that contains dense spatial information about climate and burned areas to cluster areas over Borneo.…”
Section: Introductionmentioning
confidence: 98%
“…Mustofa (2014) predicted the size of forest fires with climate variables and the forest fire weather index using the FCM clustering method that can successfully classify fire levels into three categories namely low, light and heavily burned area (Shidik & Mustofa, 2014). Jafarzadeh (2017) studied the relationship between climate and geographical variables and the fire events in Ilam Province, West of Iran. FCM was used to map all of the variables into 3 clusters, namely low, medium and high.…”
Section: Introductionmentioning
confidence: 99%
“…Mokhtari et al, 2019Ahmadi et al, 2018Jafarzadeh & Mahdavi, 2017Mokhtari et al, 2019Rostami & Kazemi, 2019Ahmadi et al, 2018Ghanavati, 2014Mokhtari et al, 2019Ahmadi et al, 2018 …”
mentioning
confidence: 99%